Eccentric exercise induces spatial changes in the mechanomyographic activity of the upper trapezius muscle - Madeleine, P.; Hansen, E. A.; Andersen, R. E.; Kumorek, M.; Mroczek, D.; Samani, A.; Kawczynski, A. (Scandinavian Journal of Medicine & Science in Sports, 2018)
In this study, we hypothesized that the recordings of multi-channel mechanomyography (MMG) of the upper trapezius muscle would reveal spatially-dependent manifestations in presence of delayed onset muscle soreness occurring 24-h after eccentric exercise (ECC). Sixteen participants performed high intensity eccentric exercises (5 sets of 10 eccentric contractions at 100% of max elevation force) targeting the upper trapezius on their dominant side. Twelve accelerometers were attached to record MMG activity during submaximal exercise consisting of static and dynamic arm flexion and abduction. Measurements were performed before and 24 h after ECC. Average rectified value (ARV), percentage of determinism (%DET) and recurrence (%REC) of the MMG signals were computed to estimate the level of muscular activity and the magnitude of regularity of the MMGs. The ARV, %REC, and %DET maps revealed heterogeneous MMG activity of the upper trapezius 24-h after ECC in comparison with before. Increased ARV, %REC and %DET were found 24-h after ECC when compared with before. The study provides new key information on how a single muscle responds to ECC. Our findings suggest that multi-channel MMG and nonlinear analyses may detect muscular and musculo-tendinous alterations due to ECC.